THE AUDITOR’S RATIONAL CHOICE OF THE AUDITOR BOARD OF THE REPUBLIC OF INDONESIA IN EXAMINING GOVERNMENT FINANCIAL REPORTS - Glory Augusta Elisabeth M. Sianipar; Lilis Ardini; Kurnia Kurnia (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract - This research aims to determine the dilemma of rational choice of auditors from the Audit Board of The Republic of Indonesia in examining government financial reports during the Covid-19 Pandemic. This research using phenomenological approach with interpretive paradigm. Methods of qualitative research were applied in this research. The method used in this research is the phenomenological approach. The subjects of this study serving as informants are those who hold functional positions as auditors within the Audit Board of the Republic of Indonesia. The findings of this study suggest that the challenge faced by the auditors of The Audit Board of The Republic of Indonesia during the Covid-19 outbreak is the auditor's dilemma when evaluating financial accounts. Limited engagement with other people is one of the challenges faced by auditors, making it challenging to gather information or data that ought to be simple. The practice of Working from Home (WFH) could frequently lead to misunderstandings with auditors. This is due to the fact that there is not any face-to-face direct communication between colleagues. Conclusion: The auditors of the Audit Board of The Republic of Indonesia always attempt to make decisions based on careful consideration and sensible choices in order to accomplish the audit objectives when performing their responsibilities. Additionally, there are concerns that emerge based on an auditor's feelings. Keywords: Auditor; Covid-19; Rational Choice Dilemma; The Auditor Board of the Republic of Indonesia